2016
DOI: 10.1111/all.12848
|View full text |Cite
|
Sign up to set email alerts
|

Prebiotic‐supplemented partially hydrolysed cow's milk formula for the prevention of eczema in high‐risk infants: a randomized controlled trial

Abstract: BackgroundPrevention guidelines for infants at high risk of allergic disease recommend hydrolysed formula if formula is introduced before 6 months, but evidence is mixed. Adding specific oligosaccharides may improve outcomes.ObjectiveTo evaluate whether partially hydrolysed whey formula containing oligosaccharides (0.8 g/100 ml) (pHF‐OS) can prevent eczema in high‐risk infants [ISRCTN65195597].MethodsWe conducted a parallel‐group, multicentre, randomized double‐blind controlled trial of pHF‐OS vs standard cow'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(80 citation statements)
references
References 25 publications
2
72
0
6
Order By: Relevance
“…As indicated before, in addition to TCR activation, costimulation and cytokine signalling play an important role in the generation of Tregs. 4 In conclusion, this study demonstrated for the first time that a specific pHP contains functional human T cell epitopes. Previously, we have shown that pre-or synbiotics may play an important role in creating the right environment for this predisposition towards Tregs.…”
Section: Hla-drb1 Allelementioning
confidence: 58%
See 1 more Smart Citation
“…As indicated before, in addition to TCR activation, costimulation and cytokine signalling play an important role in the generation of Tregs. 4 In conclusion, this study demonstrated for the first time that a specific pHP contains functional human T cell epitopes. Previously, we have shown that pre-or synbiotics may play an important role in creating the right environment for this predisposition towards Tregs.…”
Section: Hla-drb1 Allelementioning
confidence: 58%
“…1 Failure to induce oral tolerance to food proteins may result in food allergy. 4 In this study, after 6 months of intervention, increased percentages of CD4 + CD25 high Foxp3 high regulatory T cells (Tregs) and 2,3 In a recent clinical trial the preventive effect of a prebiotic supplemented partially hydrolysed whey-based infant formula (pHP) on the development of eczema in infants with increased risk of developing allergic diseases was investigated.…”
Section: Introductionmentioning
confidence: 96%
“…At 12 months, there was no difference in AD in the infants fed with study formula (07/347; 30.8%) compared to the infants fed with CMF (112/370; 30.3%; OR 0.99, 95% CI 0.71-1.37; p = 0.94). pHF-OS did not change most immune markers including total/specific IgE; however, pHF-OS reduced cow's milkspecific IgG1 ( p < 0.0001) and increased T reg cell and plasmacytoid dendritic cell percentages [81] .…”
Section: Prebioticsmentioning
confidence: 77%
“…34 A recent study also showed that avoidance of cow milk by use of an extensively hydrolysed whey formula instead did not have a protective effect in infants in developing atopy (primarily eczema) at 12 months of age. 35,36 …”
Section: Cow Milk Allergymentioning
confidence: 99%